Integrating theories of change in programme management and delivery - and Oldenbeuving, Mark (Theories of Change in Reality, 2024)
Beyond a useful tool for evaluators, theories of change can serve as an effective tool for programme delivery. However, they are often not used to their full potential. This essay will cover ways in which theories of change can be more actively used in programme management to improve programme delivery. Examples of this include using theories of action in the planning, delivery, and reporting against activities, and integrating assumptions identified in the theory of change in risk management and mitigation processes, among others. It will conclude by providing suggestions on how to practically integrate theories of change in programmes’ management information software solutions.